Pengaruh Stres Perjalanan Terhadap Motivasi Kerja Pada Karyawan Pengguna Commuter Line - Maulitya, Tannya Athalla; Muzzamil, Ferdy; Febrieta, Ditta (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The phenomenon of demotivation in the workplace is often associated with external factors, one of which is stress arising from daily commuting. This study aims to investigate the effect of commuting stress on work motivation among commuter train users. The study employs a quantitative method with purposive sampling, involving 100 respondents aged 20–45 years. The analysis reveals that commuting stress has a positive and significant effect of 56.7% on work motivation. Most respondents fall into the category of high commuting stress and high work motivation. These findings suggest that despite experiencing pressure and fatigue during commuting, many employees still demonstrate high work enthusiasm. This highlights the presence of psychological resilience or other supportive factors that can neutralize the negative effects of commuting stress. This study provides insights that commuting stress is not the sole determinant of decreased work motivation, and it is important to understand these dynamics within the context of urban workers’ daily lives.